The occurrence of Aeromonas spp. in the bottled mineral water, well water and tap water from the municipal supplies - Scoaris,Denise de Oliveira (2008)
The aim of this work was to study the occurrence of Aeromonas sp in the bottled mineral water, well water and tap water from the municipal supplies. Positive samples were found for Aeromonas spp. 12.7% from the mineral water, 8.3% from the artesian water and 6.5% from the tap water. The recovery of Aeromonas spp. was significantly higher in the bottled mineral and artesian water than in the tap water from municipal supplies. The occurrence of the Aeromonas spp. did not correlate significantly with the contamination indicator bacteria (i.e. total coliforms) in the artesian water samples. However, a significant correlation was found between Aeromonas spp. and total coliforms in the both mineral water and tap water samples. The presence or absence of a correlation between the indicator bacteria and Aeromonas could reflect the occasional appearance of the pathogen in the drinking water and the different rates of survival and recovery of these agents compared with those fecal indicators. The finding that 41.6, 14.8 and 9.0 % of the artesian water, bottled mineral water and tap water, respectively, sampled in the current study failed to meet the Brazilian standard for total coliforms in the drinking water should therefore be of concern.